Host tree traits in pasture areas affect forest and pasture specialist epiphyte species differently. Issue 4 (19th April 2021) - Elias, João P. C.; Mortara, Sara R.; Nunes‐Freitas, André F.; van den Berg, Eduardo; Ramos, Flavio N.
Abstract : Premise: Epiphytes have commensal relationships with their host trees. Besides the influence of tree traits, little has been discussed concerning the ecology of epiphytes in disturbed habitats (e.g., pasture). We herein tested whether the occurrences of pasture and forest specialist epiphytes in pastures are affected differently by tree traits. We hypothesized that (H1) the richness and abundance of generalist epiphytes would be positively associated with area availability; (H2) the richness and abundance of forest epiphyte species would be associated both with (H2.a) area availability and (H2.b) tree traits related to higher seed adherence, and/or (H2.c) less severe habitat (e.g., high humidity and more shade). Methods: We sampled 9567 epiphyte individuals from 16 species on 759 scattered remnant trees. The epiphyte species were divided into two ecological groups: forest specialists and pasture specialists. We evaluated four host tree traits: two related to tree size (crown area and trunk diameter) and two related to habitat type (crown leaf density and bark rugosity). Results: The richness and abundance of both pasture and forest specialists were positively related with tree size. However, the abundance of pasture specialists was negatively related with crown leaf density, whereas richness of forest epiphytes was positively related with bark rugosity. Conclusions: Large scattered trees tend to present higher richness and abundance of both pasture and forest specialist epiphytes compared to the smaller trees. However, high crown leaf density limits abundance of pasture specialist epiphytes, whereas rugose bark increases the richness of forest epiphytes.